1982. Multiplex PCR-Based Analysis of Enteric Pathogens in Faecal Samples from Patients with Clostridium difficile Infection in the Randomized, Controlled EXTEND Study Comparing the Efficacy of Extended-Pulsed Fidaxomicin With Vancomycin Therapy. (26th November 2018) - Wilcox, Mark; Cornely, Oliver A; Guery, Benoit; Longshaw, Christopher; Georgopali, Areti; Karas, Andreas; Kazeem, Gbenga; Palacios-Fabrega, Jose Alejandro; Vehreschild, Maria J G T
Abstract: Background: Extended-pulsed fidaxomicin (EPFX) was equivalent to standard vancomycin (SV) for resolving Clostridium difficile infection (CDI) in the EXTEND study. Sustained clinical cure (SCC) at 30 days after end of treatment (EOT) was achieved in 124/177 (70%) patients receiving EPFX vs. 106/179 (59%) patients receiving SV (difference 11%; P = 0.030). The BioFire platform, a multiplex PCR-based method, was used to detect possible enteric co-pathogens in patients from EXTEND. Methods: Patients aged ≥60 years with positive local test for CDI were randomized (1:1) to receive either EPFX (200 mg tablets, twice daily on Days 1–5 and once daily on alternate days on Days 7–25) or SV (125 mg capsules, four times daily on Days 1–10). Stool samples were collected from all patients at screening and analysed using the BioFire FilmArray Gastrointestinal (GI) panel (Biomérieux). The primary endpoint was the rate of SCC at 30 days after EOT, defined as clinical response (determined by the investigator) and no CDI recurrence. Patients were grouped according to BioFire results, and clinical outcomes were then compared using the chi-square test and logistic regression analyses. Results: At screening, all patients tested positive for C. difficile toxin A/B by local laboratory test, and 286/332 patients tested positive for C. difficile by BioFire (Figure 1). SCC rates at 30 days after EOT, by baseline presence/absence of enteric co-pathogens, are given in Figure 1, and logistic regression analyses of SCC at 30 days after EOT are given in Table 1. Conclusion: SCC-related treatment differences were evident for patients with BioFire-positive C. difficile vs. those positive for other enteric pathogens, but were not statistically significant due to low patient numbers in comparator groups. Disclosures: M. Wilcox, Astellas Pharma: Consultant and Grant Investigator, Consulting fee, Research grant, Speaker honorarium and This study was initiated and sponsored by Astellas. Medical writing support was provided by Cello Health MedErgy and funded by Astellas. O. A. Cornely, Astellas Pharma: Grant Investigator, Lecture speaker and Scientific Advisor, Research grant, Speaker honorarium and This study was initiated and sponsored by Astellas. Medical writing support was provided by Cello Health MedErgy and funded by Astellas. B. Guery, Astellas Pharma: Consultant, Consulting fee and This study was initiated and sponsored by Astellas. Medical writing support was provided by Cello Health MedErgy and funded by Astellas. C. Longshaw, Astellas Pharma: CL was a full-time employee of Astellas Pharma, Inc., during the study conduct and is now an employee of Shionogi Europe Ltd.; he also has a patent WO2015169451 A1 pending. and Employee, Medical writing support was provided by Cello Health MedErgy and funded by Astellas. and Salary. A. Georgopali, Astellas Pharma: Employee, Medical writing support was provided by Cello Health MedErgy and funded by Astellas. and Salary. A. Karas, Astellas Pharma: AK has patents WO2015169451 A1 and EP17167541.6 pending. and Employee, Medical writing support was provided by Cello Health MedErgy and funded by Astellas. and Salary. G. Kazeem, Astellas Pharma: Independent Contractor, Medical writing support was provided by Cello Health MedErgy and funded by Astellas. and Salary. J. A. Palacios-Fabrega, Astellas Pharma: AP-F has a patent EP17167541.6 pending. and Employee, Medical writing support was provided by Cello Health MedErgy and funded by Astellas. and Salary. M. J. G. T. Vehreschild, Astellas Pharma: Consultant and Grant Investigator, Consulting fee, Grant recipient and This study was initiated and sponsored by Astellas. Medical writing support was provided by Cello Health MedErgy and funded by Astellas.